BOOK REVIEW OF EVERYTHING SHE TOUGHT SHE WANTED By ELIZABETH BUCHAN - Mawarni, Endah (LANTERN (Journal on English Language, Culture and Literature), 2015)
Women have always been interesting things to be discussed.Awoman’s heart is a deep ocean secret. And life always gives new stories, something that was unpredictable to be a part of the secret. Then, their story retold in a literary work called novel to inspire women around the world.A novel that the writer will discuss is written by Elizabeth Buchan, titled Everything She Thought She Wanted. This novel totaling 386 pages, published in 2004 by Penguin Books as That Certain Age in Great Britainand first published in the United States of America by Viking Penguin in 2005 and by Penguin Books in 2006 as Everything She Thought She Wanted. This novel has a feminist cover with the unique design and imagesof women stuff that reflects a conventional and modern style. The writer chooses Everything She Thought She Wanted to be reviewed because the writer finds it interesting to discuss about love and independence in this novel as the theme.